2013
DOI: 10.3144/expresspolymlett.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

A versatile characterization of poly(N-isopropylacrylamide-co-N,N'-methylene-bis-acrylamide) hydrogels for composition, mechanical strength, and rheology

Abstract: Poly(N-isopropylacrylamide-co-N,N'-methylene-bisacrylamide) (P(NIPAAm-co-MBA)) hydrogels were prepared in water using redox initiator. The copolymer composition at high conversion (> 95%) was determined indirectly by HPLC (high performance liquid chromatography) analysis of the leaching water and directly by solid state 13C CP MAS NMR (cross polarization magic angle spinning nuclear magnetic resonance) spectroscopy of the dried gels, and was found to be close to that of the feed. The effect of cross-linker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…After the plasma copolymerization process, the obtained polymeric coatings are immersed in distilled water for 24 h to remove pNIPAAm and poly( N , N ″‐methylene‐bis‐acrylamide) (pMBA) homopolymers and non‐reacted NIPAAm and MBA monomers as they are all water soluble in contrast to p(NIPAAm‐co‐MBA) . During this purification process, water was refreshed every few hours and pure p(NIPAAm‐co‐MBAm) coatings are finally obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the plasma copolymerization process, the obtained polymeric coatings are immersed in distilled water for 24 h to remove pNIPAAm and poly( N , N ″‐methylene‐bis‐acrylamide) (pMBA) homopolymers and non‐reacted NIPAAm and MBA monomers as they are all water soluble in contrast to p(NIPAAm‐co‐MBA) . During this purification process, water was refreshed every few hours and pure p(NIPAAm‐co‐MBAm) coatings are finally obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The initial results implied that the pNIPAAm coatings possessed an asymmetric structure with a complex mixture of NIPAAm monomers and lineal pNIPAAm homopolymers apart from pNIPAAm crosslinked network situated in the outer layer of the coatings. It is already known that the polymerization of NIPAAm in the presence of crosslinking monomers improves the mechanical properties and response rate of pNIPAAm hydrogels . On the other hand, an excessive crosslinking may compromise the swelling properties and porosity of the hydrogel thus diminishing its potential for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Chetty and co-workers investigated the relation between the initial monomer composition and the composition of the formed cross-linked PNIPAAm hydrogel. It has been found that the copolymer gel composition was very close to the initial monomer composition [20]. Therefore the copolymer cross-link density can also be expressed with the monomer to cross-linker ratio, namely with the R values, i.e.…”
Section: Introductionmentioning
confidence: 85%
“…For determining the LCST turbidimetry, calorimetry, light scattering, nuclear magnetic resonance spectroscopy (NMR), oscillation rheometry [20], fluorescence spectroscopy, Fourier transform infrared spectroscopy may be used [21].…”
Section: Introductionmentioning
confidence: 99%
“…Chetty and co-workers observed that the critical strain increases from 1.6% to 7.9% with increasing cross-linker ([BIS]/[NIPAAM]) concentration from 0.01 to 0.1. 41 However, in the present system the critical strain increases from 203% to 584% with the addition of 3 mM R solution. This signicant increase of critical strain is an interesting observation particularly for the case of supramolecular crosslinking.…”
Section: Mechanical Propertiesmentioning
confidence: 96%